Is China a House of Islam?: Chinese Questions, Arabic Answers, and the Translation of Salafism from Cairo to Canton, 1930-1932 - Halevi, Leor (Die Welt des Islams, 2019)
Rashīd Riḍā's six fatwas to China, disregarded by historians of China and by historians of Salafism, greatly expand our historical understanding of transnational intellectual exchanges between Muslim reformers in the interwar period. The questions that prompted the fatwas shed new light on the specific issues that divided Sino-Muslim nationalists in the republican era, when a Chinese awakening coincided with an Islamic awakening. They also reveal why a Sino-Muslim scholar, seeking external arbitration, decided to write to a Muslim authority in Cairo. The fatwas that ensued show, in turn, the care that Riḍā took to transmit his legal methods and religious values to a foreign country, where Muslims mainly followed the Ḥanafī school of law. On the basis of the fatwas, which were translated into Chinese, the article offers not an arbitrary, abstract, or ahistorical understanding of the origins of Salafism in China, but a concrete grasp of Salafism in translation.